2008
DOI: 10.1177/0146167207309192
|View full text |Cite
|
Sign up to set email alerts
|

Are Women Always More Interpersonally Sensitive Than Men? Impact of Goals and Content Domain

Abstract: Two studies examined motivation and content domain as possible influences on sex differences in interpersonal sensitivity. Although much research has found women to excel on tasks measuring interpersonal sensitivity, most of the tasks have measured accuracy in female-relevant domains such as emotion. The present studies measured interpersonal sensitivity, defined as accurate recall of another person, for both female-relevant and male-relevant content domains and also included motivational manipulations intende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
79
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(97 citation statements)
references
References 48 publications
(65 reference statements)
9
79
0
4
Order By: Relevance
“…Yet the gender of the perceiver did matter: men performed significantly worse on the empathic accuracy task than women. Although this finding is consistent with some past research that has found gender differences in empathic accuracy (Galinsky et al, 2006, Study 3;Hall, 1978), evidence suggests that such differences may not necessarily be hard-wired, but rather can be attributed to more fluid contextual and individual difference variables, such as the motivation to be empathic (Hall & Mast, 2008;Ickes, Gesn, & Graham, 2000;Klein & Hodges, 2001). Consistent with this view, we found that the gender difference was statistically mediated by the two individual difference predictors of empathy:…”
Section: Gender Differences In Empathic Accuracysupporting
confidence: 92%
“…Yet the gender of the perceiver did matter: men performed significantly worse on the empathic accuracy task than women. Although this finding is consistent with some past research that has found gender differences in empathic accuracy (Galinsky et al, 2006, Study 3;Hall, 1978), evidence suggests that such differences may not necessarily be hard-wired, but rather can be attributed to more fluid contextual and individual difference variables, such as the motivation to be empathic (Hall & Mast, 2008;Ickes, Gesn, & Graham, 2000;Klein & Hodges, 2001). Consistent with this view, we found that the gender difference was statistically mediated by the two individual difference predictors of empathy:…”
Section: Gender Differences In Empathic Accuracysupporting
confidence: 92%
“…Traditionally, women are considered to be more emotional, to experience and express their emotional states more intensely (Brody & Hall, 1993), to report greater emotional awareness (Feldman-Barrett, Lane, Sechrest, & Schwartz, 2000), to perform better on emotion perception tasks (McClure, 2000;Montagne, Kessels, Frigerio, de Haan, & Perrett, 2005), to show a greater sensibility to relationships and interpersonal regulation (Hall & Mast, 2008), and to inform a greater empathetic disposition than men (Mestre, Samper, Frías, & Tur, 2009). These findings have made it evident that women usually score higher than men in the affective sphere.…”
Section: Gender Differences In Ei and Well-being Indexesmentioning
confidence: 99%
“…Tradicionalmente las mujeres son consideradas más emocionales, experimentan y expresan sus estados anímicos más intensamente (Brody y Hall, 1993), informan de mayor conciencia emocional (Feldman-Barrett, Lane, Sechrest, y Schwartz, 2000), rinden mejor en tareas de percepción de emociones (McClure, 2000;Montagne, Kessels, Frigerio, de Haan, y Perrett, 2005), muestran una mayor sensibilidad relacional y regulación interpersonal (Hall y Mast, 2008) así como una mayor disposición empá-tica que los varones (Mestre, Samper, Frías, y Tur, 2009). Estos hallazgos ponen de manifiesto que en el terreno afectivo las mujeres suelen puntuar más alto que los hombres en diferentes ámbitos, por lo que, sería lógico pensar que en las habilidades emocionales integradas en el concepto de IE, las mujeres deberían mostrar niveles más elevados que los hombres, lo cual aportaría evidencias sobre la validez de constructo del concepto (Fernán-dez-Berrocal, Cabello, Castillo, y Extremera, 2012).…”
Section: Diferencias De Género En Inteligencia Emocional Y Variables unclassified
“…Although there is evidence of women outperforming men in interpersonal accuracy tasks (Hall, 1984(Hall, , 2006Hall & Schmid Mast, 2008;McClure, 2000), women do not seem to have an advantage in judging dominance or power in others as compared to men (Schmid Mast & Hall, 2004b;. Perhaps men have greater accuracy because power is a male-typical issue, and men might be more expert in power issues than women because they are more competitive (Bjorkqvist, Lagerspetz, & Kaukiainen, 1992;Eagly, Karau, Miner, & Johnson, 1994), more easily form hierarchies when they first meet (Schmid Mast, 2001, 2002b, and are more motivated to take on the leadership role (Eagly et al, 1994).…”
Section: Accuracy Of Assessing Powermentioning
confidence: 99%
“…Or, women may be particularly bad at judging power (as compared to judging emotions, in which they do a better job than men) because they are comparatively non-experts, or any combination of the above. There is some evidence to suggest that men's accuracy was increased when the situation was related to power than if the situation was not (i.e., they had to remember the opponent's performance in a competitive task as compared to a cooperative task; Hall & Schmid Mast, 2008).…”
Section: Accuracy Of Assessing Powermentioning
confidence: 99%